Examining the relationship between alcohol use and high-risk sex practices in a population of women with high HIV incidence despite high levels of HIV-related knowledge. (15th January 2014) - Zetola, Nicola M; Modongo, Chawangwa; Olabiyi, Bisayo; Ramogola-Masire, Doreen; Collman, Ronald G; Chao, Li-Wei
Abstract : Objectives: Alcohol use has been linked to risky sexual behaviour and it has been identified as an important modifiable factor to prevent HIV infection. However, the evidence of a link between alcohol use and risky sexual behaviour is mixed. In this paper, we examine the role of alcohol use in sexual risk taking among women in Botswana. Methods: Participants were recruited by stratified proportional random sampling and were administered a survey interview that collected information on HIV/AIDS knowledge, risky sexual behaviour and alcohol use. Logistic regression and bivariate probit analyses were used to examine the association between alcohol use and high-risk sexual behaviour. Results: 239 women were interviewed. 168 (70%) had high levels of HIV/AIDS knowledge. We found no significant protective effect of good HIV/AIDS knowledge over high-risk sex behaviour (adjusted OR 0.74, 95% CI 0.38 to 1.42). However, alcohol use before sex was associated with high-risk sex behaviour (adjusted OR 3.04, 95% CI 1.11 to 6.45). However, bivariate probit analysis that simultaneously estimates risky sexual behaviour and alcohol use revealed an insignificant association between alcohol use and risky sex, highlighting the potential presence of other unobserved individual factors that are associated with alcohol use and risky sex. Conclusions: Knowledge about HIV may not be sufficient to decrease risky sexual behaviour. Alcohol consumption was associated with an increased probability of high-risk sexual intercourse. However, the relationship between alcohol use and risky sex may also be a marker of a third omitted variable (such as overall risk-taking propensity). Further research is needed to identify factors associated with alcohol use and high-risk sex.